Implementation of Ethnoscience-Based PjBL on Science Literacy Learning Outcomes - Anisatul Hidayah; Mohamad Agung Rokhimawan; Rudi Suherman (Yayasan Keluarga Guru Mandiri, 2024)
Science education develops quickly and is rooted in the 21st Century. The learning carried out focuses on active students and produces something with PJBL. This study determines how Ethnoscience-based PJBL learning impacts scientific literacy learning outcomes. The study used a descriptive qualitative method. Data collection techniques used interviews, observation, and documentation. This study used descriptive analysis methods through data reduction, data presentation, and conclusions drawing. The study results show that students’ scientific literacy learning outcomes using Ethnoscience-based PJBL can deliver students with processing abilities, scientific attitudes, communicating results, and paying attention to socio-culture in the area around students. Using this PJBL facilitates students to gain knowledge and skills through project development and implementation involvement. Projects with complex assignments will encourage students to design, solve problems, make decisions, and display ethnoscience-based products by combining culture with science in the learning process.